Stroke risk stratification in patients with heart failure and sinus rhythm . (26th August 2022) - Sagris, Dimitrios; Shantsila, Eduard; Lip, Gregory Y H
Graphical Abstract: Graphical Abstract Patients with heart failure and reduced ejection fraction in sinus rhythm and atrial fibrillation. Patients with sinus rhythm who were stratified in the highest quintile based on the S2I2N0–3 score had similar ischaemic stroke rates to patients with heart failure and reduced ejection fraction and atrial fibrillation who were not treated with oral anticoagulation. HFrEF, heart failure and reduced ejection fraction; OAC, oral anticoagulation.